Determinants of the factors that cause abandoned housing projects: a study of human buyers of Islamic home financing in Malaysia - Abdul Razak, Dzuljastri (2015)
The issues of abandoned housing projects are not new in Malaysia. Without proper measures to tackle, they will continue to haunt home buyers. This study examines responses of 328 customersobtained by means of self-administered questionnaires. Four variables namely lack of justice and equity, methods of computing and pricing, nature of contract and lack of legal and governance were used as variables. The results indicated that all the hypothesized relationships are supported. Of these, the nature of contract was found to be the main cause of the problem. The results contributes to the scanty empirical research in this area. It also benefits managers of Islamic banks to address issues that are affectingabandoned housing projects in Malaysia.